(untitled) (The Review of Diabetic Studies, 2025)
Background Airborne transmission of respiratory pathogens, such as SARS-CoV-2 and influenza, poses significant risks in healthcare settings, contributing to millions of healthcare-associated infections (HAIs) annually, with economic burdens exceeding 200 billion in high-income countries. Advanced HVAC systems integrated with HEPA filtration (H13-H14, >99.95% efficiency at 0.3 μm) emerge as key interventions to capture aerosols and dilute contaminants, addressing historical gaps exposed by pandemics like 1918 influenza and COVID-19.​ Methods This narrative review synthesizes evidence from pre- and post-COVID studies, including RCTs, CFD models, Wells-Riley simulations, and bioaerosol chamber experiments, scoping HVAC-HEPA efficacy across hospitals, schools, and low-resource settings. It examines mechanisms (impaction, interception, diffusion), performance data (log10 reductions), and standards (ASHRAE 170, EN 1822).​ Results HEPA filtration achieves 2-5 log10 reductions in viral aerosols, clearing SARS-CoV-2 >99.97% after 7 air volumes; HVAC-HEPA combos with 6-12 ACH reduce infection risks 40-90%, outperforming standard ventilation. Real-world deployments lowered HAIs and bioaerosols by 70-90% in ICUs and wards.​ Conclusions Advanced HVAC-HEPA systems provide robust, cost-effective mitigation against respiratory pathogens, warranting widespread adoption despite challenges like filter loading. Future longitudinal RCTs and AI-nanofilter innovations will optimize implementation.